2022
DOI: 10.7203/drdcd.v1i8.223
|View full text |Cite
|
Sign up to set email alerts
|

Feminist discourses of Spanish digital influencers: An analysis of their activity on social media

Abstract: With the rise of digital feminism, this article explores the role of Spanish digital influencers considered as feminist referents and the topics addressed by them on social networks from a gender perspective. An online survey was used to create a ranking of the twelve most popular influencers by social media users. Firstly, an analysis of their professional and sociodemographic profiles was made. Secondly, a cross-platform content analysis of the posts published by these influencers on Facebook, Twitter and In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…More generally, the article adds to recent scholarly debates on ‘influencer creep’ (Bishop, 2022) by exploring the extent to which influencing culture creeps into various practices and forms of work, including political activism. My analysis also adds to the growing scholarly and public interest in the entanglements between contemporary forms of political activism and influencer culture (Novoselova and Jenson, 2019; Brown, 2022; Navarro and Villegas-Simón, 2022; Semenzin, 2022; Dean, in press), which in turn sheds light on the interplay between digital feminist activism and neoliberalism (Baer, 2021; Scharff, 2023a). My approach to neoliberalism is Foucauldian and informed by analyses which have demonstrated that neoliberalism entails the expansion of market principles to all areas of life.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…More generally, the article adds to recent scholarly debates on ‘influencer creep’ (Bishop, 2022) by exploring the extent to which influencing culture creeps into various practices and forms of work, including political activism. My analysis also adds to the growing scholarly and public interest in the entanglements between contemporary forms of political activism and influencer culture (Novoselova and Jenson, 2019; Brown, 2022; Navarro and Villegas-Simón, 2022; Semenzin, 2022; Dean, in press), which in turn sheds light on the interplay between digital feminist activism and neoliberalism (Baer, 2021; Scharff, 2023a). My approach to neoliberalism is Foucauldian and informed by analyses which have demonstrated that neoliberalism entails the expansion of market principles to all areas of life.…”
mentioning
confidence: 89%
“…Likewise, researchers have observed a ‘growing convergence between politics and micro-celebrity/influencer culture’ (Dean, in press: 26). Terms such as ‘feminist influencers’ (Novoselova and Jenson, 2019; Navarro and Villegas-Simón, 2022), ‘activist influencers’ (Semenzin, 2022), and analyses of how influencers engage in social justice ecologies (e.g. Abidin and Cover, 2019) attest to a growing interest in how contemporary protest cultures, including feminist activism, are shaped by the neoliberal digital economy.…”
mentioning
confidence: 99%